EKRANISASI NOVEL YOGISHA X NO KENSHIN KARYA KEIGO HIGASHINO - Sinambela, Reski Amalia; Anwar, Fithyani ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2025)
Popular novels are often adapted into a film. One of the novels adapted into a film with the same title is Yogisha X no Kenshin by Keigo Higashino. The adaptation of this novel resulted in changes to the plot elements, characters, and setting, which impacted audience satisfaction with the film. This research uses a qualitative descriptive method and a structural approach to analyze the process of adapting Yogisha X no Kenshin into a film and identify changes between the novel and film versions. Data was obtained from reading novels and watching films, then analyzing changes in plot, characters, and settings. This research shows that the adaptation process resulted in changes to the story structure; namely, in the plot aspect, there were 28 reductions, 17 additions, and 14 variations. In the character aspect, there are three subtractions, two additions, and six variations of changes. Meanwhile, in the background aspect, there is one reduction, four additions, and 13 variations of changes. The impact of the adaptation process provides different interpretations for viewers of the two works. Nevertheless, the adaptation process as a whole had a positive impact, as seen from the audience's positive response to the adaptation.